2020
DOI: 10.1007/s00330-020-06829-2
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic model for coronavirus disease 2019 (COVID-19) based on radiological semantic and clinical features: a multi-center study

Abstract: Objectives Rapid and accurate diagnosis of coronavirus disease 2019 is critical during the epidemic. We aim to identify differences in CT imaging and clinical manifestations between pneumonia patients with and without COVID-19, and to develop and validate a diagnostic model for COVID-19 based on radiological semantic and clinical features alone. Methods A consecutive cohort of 70 COVID-19 and 66 non-COVID-19 pneumonia patients were retrospectively recruited from five institutions. Patients were divided into p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 26 publications
6
134
0
3
Order By: Relevance
“…In our previous study, we demonstrated that based on CT imaging and clinical manifestations alone, the pneumonia patients with and without COVID-19 can be distinguished (11). Harrison et al…”
Section: Introductionmentioning
confidence: 92%
“…In our previous study, we demonstrated that based on CT imaging and clinical manifestations alone, the pneumonia patients with and without COVID-19 can be distinguished (11). Harrison et al…”
Section: Introductionmentioning
confidence: 92%
“…[84][85][86][87] When the COVID-19 epidemic erupted in China, clinicians lacked access to rRT-PCR kits and then as rRT-PCR became available, low rRT-PCR sensitivity reinforced belief in the additive value of CT for many. 88 These observations and scenarios prompted some to advocate for CT as a first-line supplement to the diagnostic evaluation for COVID-19, combining rRT-PCR with CT. 89,90 If CT alone or in combination with rRT-PCR reduced false-negative rates, the positive public health implications for case identification and control of disease transmission could be substantial. However, these benefits must be balanced against the cost of CT, medical radiation dangers, or practical limitations in busy hospitals with hourly trauma and stroke arrivals and potentially time-dependent emergencies juxtaposed against advised CT shutdowns for COVID-19 cleaning requiring 30 or more minutes.…”
Section: Antigen Testsmentioning
confidence: 99%
“…Previous studies have reported prediction models for diagnosis and prognosis of COVID-19 and for detecting the risk of being admitted to a hospital for COVID-19. Chen et al constructed a diagnosis prediction model with 10 clinical factors based on 136 participants [22]. Wang et al enrolled 296 in-hospital patients with COVID-19 and developed a clinical model to predict the mortality of such patients [20].…”
Section: Discussionmentioning
confidence: 99%